2011
DOI: 10.1016/j.enpol.2011.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Split incentives and energy efficiency in Canadian multi-family dwellings

Abstract: This paper examines the energy-related behaviour of occupants and owners of multifamily dwellings in Canada, some of whom do not pay directly for electricity or heat, but instead have these costs included in their rent or condo fees. Using data from the 2003 Survey of Household Energy Use, we look at the extent to which split incentives that result from bill-paying arrangements effect a variety of activities including the setting of temperatures at various times of the day and the use of eco-friendly options i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 6 publications
3
37
0
Order By: Relevance
“…No mention is made, for instance, of split incentives around energy efficiency [48], which would have presented the opportunity to discuss this as an important contextual issue. We also detected, despite arguments discussed in section 2.2 about issues above the level of the individual being addressed in the reviewed guidance, the consumer was referenced far more frequently than other actors in the supply chain such as manufacturers or retailers of electrical goods.…”
Section: Discussionmentioning
confidence: 99%
“…No mention is made, for instance, of split incentives around energy efficiency [48], which would have presented the opportunity to discuss this as an important contextual issue. We also detected, despite arguments discussed in section 2.2 about issues above the level of the individual being addressed in the reviewed guidance, the consumer was referenced far more frequently than other actors in the supply chain such as manufacturers or retailers of electrical goods.…”
Section: Discussionmentioning
confidence: 99%
“…Davis (2012) employed data from the 2005 RECS and a linear probability model to study the importance of principal-agent problems in EE appliances and lighting and demonstrated the effectiveness of command-and-control approaches. Maruejols and Young (2011) used data from the 2003 Canadian 'Survey of Household Energy Use' to study energy-related behavior in multi-family dwellings. Their results indicate that households not paying heating bills directly chose higher temperature settings.…”
Section: Literaturementioning
confidence: 99%
“…Tenants who sign energy-inclusive rental agreements face zero marginal cost from energy consumption, and therefore may use too much energy, relative to the social optimum. Indeed, tenants appear to keep indoor temperatures higher during winter months and when their homes are unoccupied when utilities are included in their leases (Maruejols and Young 2011;Levinson and Niemann 2004). Likewise, tenants who pay for utilities are more likely to adjust heating temperatures at night than tenants who face zero marginal cost (Gillingham, Harding, and Rapson 2012).…”
mentioning
confidence: 99%